TRADING BEHAVIOR OF HOUSEHOLD INVESTORS IN THE IMMEDIATE IPO AFTER-MARKETS - Salo, Matti (My University, 2004)
The purpose of this thesis is to study the investment patterns and subsequent returns of household investors in the immediate after-markets of IPOs conducted in the Finnish stock markets during the time period of October 1998 − December 2000. The emphasis is on contrarian investment strategies, poor investment returns and herd behavior, that are all evidenced by earlier studies to be especially apparent with household investors. The theoretical part of the study presents the related framework of theoretical models and earlier studies starting from the basic outline of market efficiency and ending to the finesses of behavioral finance studies related to the study focus. The sample used in this study consists of original matched order data on the first trading days of 36 IPOs, and the subsequent close-to-close returns for the consequent year. The statistical methods used in this study enclose, in addition to the tests for normality, Student´s t-test, one-way ANOVA, and from the non-parametrical side, Mann-Whitney and Kruskal-Wallis tests. Contrarian investment pattern on the first trading days among the household investors is not found. It rather seems that households are always on the buy side regardless of the direction of the stock price or the magnitude of it. Only slight support is given to the hypothesis, that the stocks households sell outperform the stocks they buy. Of the calculated holding periods, the 12 month holding period this is the only one that conforms to the research hypothesis. Finally, no support is found to the suggestion that household trading fraction would be negatively correlated with the subsequent returns.
Keywords: IPO; contrarian; household investor; investor behavior; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|